Church music as pedagogy: an investigation through digital storytelling into the role that Southern African Christian Church music praxis played in the musical development of five professional musicians - Mathebula, Praise Ntsako (Rhodes University, Faculty of Humanities, Department of Music and Musicology)
Using an ethnographic and autoethnographic approach, this study investigated how the church has influenced the development and practice of five professional musicians practicing in South Africa. This research resulted from discussions with numerous musicians who had their music genesis at church, some of them well-known professionals in the country. Reflecting on the history of church music education that can be traced back to the arrival of the missionaries on the African continent and the different types of music education settings that can be found in South Africa, this thesis analyses the approach and delivery of music pedagogy that exists in the South African church setting. Discussing the introduction of Western musical tools such as tonic-solfa, choral music and four-part singing, this research contextualises the historical effect of mission education of several South African composers, including Tiyo Soga, Enoch Sontonga and John Knox Bokwe. Thereafter, using Digital Storytelling (DS) as a methodology for data collection and Ethnographic Content Analysis (ECA) as an analytic tool, co-researchers were given the opportunity to create data or share their stories in a novel manner, which has proven to develop powerful, honest and self-reflexive results. Important pedagogic themes that emerged as being part of a shared church-led approach to music teaching and learning include practice and consistent performance; collaboration; imitation; embodied and experiential learning, rote learning, and memorisation. Central to using DS as a methodology, this study found that musical identity and early pedagogical approaches to learning music play an important factor in further musical development and education.
Keywords: Church music -- Africa, Southern; Indigenous music; Digital storytelling; Music -- Southern Africa; Musicians -- Africa, Southern; Western education